Negative impact of oral exposure to polystyrene microplastics on glucose tolerance and intestinal environment in mice is independent of particle size - Yuto Saijo; Yuka Hasegawa; Takuro Okamura; Yuriko Ono; Takahiro Ichikawa; Naoko Nakanishi; Yutaro Tsuchimura; Tamaki Morioka; Shuhei Tanaka; Hirohisa Takano; Masahide Hamaguchi; Michiaki Fukui (Environmental Sciences Europe)
Abstract Background Surging plastic pollution poses health issues worldwide. As the production of plastics has been skyrocketing, the impact of microplastics (MPs) on ecosystems is no longer negligible. Our previous study revealed that oral administration of MPs to mice impaired glucose tolerance in the presence of leaky gut syndrome (LGS) induced by a high-fat diet (HFD). This study aimed to elucidate the effect of particle size of MPs on toxicity, specifically against glucose metabolism, in HFD-fed mice. C57BL6/J mice were assigned to four groups: one fed a HFD alone, and three fed a HFD mixed with polystyrene MPs (PS-MPs) of different particle sizes (0.5, 10, and 100 µm) for 6 weeks. The dose of PS-MPs administered was 10 mg/kg BW/day. We analyzed glucose tolerance, histological and immunochemical changes in the intestinal tract, gene expression in the small intestine, and gut microbiota. Results Regardless of particle size, PS-MPs compromised glucose tolerance in mice. Relative atrophy of the intestinal villi and an increased number of macrophages and natural killer cells were observed in mice administered with PS-MPs. The expression of genes related to glucose metabolism and inflammation in the murine jejunum was altered in mice administered PS-MPs. In HFD + PS-MP 10 µm mice, both composition and diversity of gut microbiota altered, and in HFD + PS-MP 0.5 and 100 µm mice, composition of gut microbiota changed. Conclusion Regardless of particle size, oral exposure to PS-MPs triggered impaired glucose tolerance, inflammation in the intestinal tract, and alterations in gene expression and gut microbiota. This study underscores the necessity of mitigating oral exposure to MPs regardless of particle size. Graphical Abstract